JCET Companion: Mobile Application for Campus Assistance - A, Ajith; R, Aswin A; V, Atul; K, Kishor P; Visakh, Divya (Journal of Trends in Computer Science and Smart Technology, 2024)
JCET (Jawaharlal College of Engineering and Technology) Companion, the innovative mobile app thoughtfully designed for JCET college community, introduces a comprehensive suite of indispensable features aimed at simplifying and enhancing campus life. At its core, the app provides a user-friendly event calendar intricately linked with a reminder system, ensuring students never miss vital dates or essential college events. The meticulously organized study material empowers efficient learning, while crucial announcements keep users informed. With seamless attendance tracking and notifications, students stay accountable and punctual. Homework management, to-do lists, fee handling through an integrated gateway, and efficient leave request management all find a home in this app, uncluttering the daily tasks that typically burden students. In essence, JCET Companion offers a centralized platform, fostering a sense of community and shared experience while ensuring everyone is consistently up to date, transforming college life into a well-organized and informed journey, marked by enhanced efficiency and connectivity for all its users.
Keywords: Attendance Tracking And Notifications; Homework Management; Fee Handling; To-Do-List; Leave Request; Mobile Application